2009
DOI: 10.1016/j.yebeh.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Subventricular zone-derived, newly generated neurons populate several olfactory and limbic forebrain regions

Abstract: Neurogenesis persists in several regions of the adult mammalian brain. Although the hippocampus and olfactory bulb are most commonly studied in the context of adult neurogenesis, there is an increasing body of evidence in support of neurogenesis occurring outside of these two regions. The current study expands upon previous data by showing newborn neurons with a mature phenotype are located in several olfactory and limbic structures outside of the hippocampus and olfactory bulb, where we previously described D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 64 publications
1
71
2
2
Order By: Relevance
“…Recent studies suggest the presence of adult-born neurons or immature neurons in several regions of the adult mammalian central nervous system outside the canonical neurogenic niches, including cortical areas (Kaplan, 1981;Dayer et al, 2005;Takemura, 2005;Shapiro et al, 2007aShapiro et al, , 2007bShapiro et al, 2009;de la Rosa-Prieto et al, 2010), subcortical areas (Bédard et al, 2002;Bernier et al, 2002;De Marchis et al, 2004;Vessal et al, 2007;Okuda et al, 2009;Pierce and Xu, 2010;Ehninger et al, 2011;Dirian et al, 2014;Ernst et al, 2014;Luzzati et al, 2014), and the spinal cord (Shechter et al, 2007). In humans, histological and carbon-14 dating approaches revealed that adult-born interneurons could integrate into the striatum (Ernst et al, 2014).…”
Section: Neurogenesis In the Adult Mammalian Brain: A Controversial Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest the presence of adult-born neurons or immature neurons in several regions of the adult mammalian central nervous system outside the canonical neurogenic niches, including cortical areas (Kaplan, 1981;Dayer et al, 2005;Takemura, 2005;Shapiro et al, 2007aShapiro et al, , 2007bShapiro et al, 2009;de la Rosa-Prieto et al, 2010), subcortical areas (Bédard et al, 2002;Bernier et al, 2002;De Marchis et al, 2004;Vessal et al, 2007;Okuda et al, 2009;Pierce and Xu, 2010;Ehninger et al, 2011;Dirian et al, 2014;Ernst et al, 2014;Luzzati et al, 2014), and the spinal cord (Shechter et al, 2007). In humans, histological and carbon-14 dating approaches revealed that adult-born interneurons could integrate into the striatum (Ernst et al, 2014).…”
Section: Neurogenesis In the Adult Mammalian Brain: A Controversial Tmentioning
confidence: 99%
“…Innovative and meticulous studies have led to the identification of at least three different cell types that give rise to new neurons outside the canonical neurogenic niches of the (healthy) adult mammalian brain. The first was BrdU-positive neuroblasts emigrating from the subventricular zone, which are reported to give rise to a small number of new-born neurons in some ventral brain regions in the early to young postnatal period in mice and rats (De Marchis et al, 2004;Shapiro et al, 2007a;Shapiro et al, 2007b;Shapiro et al, 2009), as well as in young rabbits and monkeys, where the migratory routes of these immature neurons are well documented (Bédard et al, 2002;Bernier et al, 2002;Luzzati et al, 2003). However, since this form of neurogenesis was only observed in the very early postnatal period in these mammals, critics stated that this low-level neurogenic process was merely a protraction of an incomplete developmental neurogenesis (reviewed in Bonfanti and Peretto, 2011).…”
Section: Limits and Ambiguities Of Cell-proliferation Assays Used To mentioning
confidence: 99%
See 1 more Smart Citation
“…Neurônios que se originam na SVZ migram para o bulbo olfatório [5][6][7] . Novos neurônios residindo na SVZ também entram no neocórtex de associação (córtices pré-frontal, temporal inferior e parietal posterior) 8 , estriado 6 , córtex piriforme 9 , amídala e córtex entorrinal lateral 10 . Tem sido relatado que a neurogênese ocorre em outras áreas do cérebro adulto, tais como neocórtex 11,12 , sub-regiões CA do hipocampo (CA1, CA2-3) 13 , amídala, córtex piriforme 12 , substância negra 14 e III ventrículo 15 , mas esses dados têm sido fonte de debates e controvérsias e ainda precisam ser confirmados.…”
Section: Introductionunclassified
“…It is also important in processing information about pheromones and other olfactory or vomeronasal input, causing it to directly influence the endocrine system (Halpern and Martínez-Marcos, 2003) and behavior during confrontations with conspecifics (agonistic behavior) (Meredith and Westberry, 2004). Support for mammalian amygdalar neurogenesis has been limited to studies indicating proliferation, cell genesis, and specification in Orictolagus cuniculus (New Zealand white rabbits) (Luzzati et al, 2006), Mus musculus (laboratory mice) (Shapiro et al, 2009), and Saimiri sciureus (common squirrel monkeys) and Macaca fascicularis (crab-eating macaques) (Bernier et al, 2002). In the present study I have found the reptilian DLA/LA is a region of high proliferation, but low migration and survival, which coincides with its role, not in storage, but in encoding sensory memory.…”
Section: Amygdaloid Regionsmentioning
confidence: 99%